Sơ đồ BATS và ứng dụng trong việc tính các dòng trao đổi năng lượng và nuwocs giữa bề mặt đất - khí quyển - Tân, Phan Văn; Điền, Nguyễn Hướng; Tiến, Dư Đức (VNU Journal of Science: Natural Sciences and Technology, 2004)
In this study we use BATS scheme to investigate the energy and water fluxes between land surfaces and atmosphere with five different scenarios, denoted by THI, TH2, TH3a, TH3b and TH4. Four types of vegetation/land - cover are chosen, which consist of crop (Si), evergreen needle leaf tree (S2), evergreen broadleaf tree (S4), and tall grass (S4). For each scenario, set of parameters representing characters of vegetation/land-cover types, atmospheric forces, such as the fractional vegetation cover, the initial values of soil moisture in soil layers, the precipitation rate and frequency, are given. The results showed that, latent heat, sensitive heat fluxes and run - off are rather sensitive with land surface types. In the same driving forces of atmosphere, fluxes from/to the land surface with larger of fractional vegetation cover are stronger. The increase of precipitation rate (TH2) lead to much more increasing run - off from surface type of S3 than other. In the case of long time without precipitation, sensitive heat fluxes from land surface types to atmosphere are strongly increased. i